Nesting Sites Apis cerana Fabr. (Hymenoptera: Apidae) in Two Different Altitutes of Polyculture Plantations in West Sumatera - . JASMI; SITI SALMAH; . DAHELMI; . SYAMSUARDI (Bogor Agricultural University, Indonesia, 2014)
Natural cavities in polyculture plantations are important for the conservation of honeybees. This study was aimed to determine the diversity, nest sizes, and fluctuations in the use of sites for nesting by Apis cerana Fabr. in polyculture plantations in two altitudes in West Sumatra. A census method was used to obtain the data variables in 10 plantations (five locations for each altitute). Polyculture plantations used as the study sites were dominated by coconut in lowland areas and coffea in highland areas. The results showed that nesting sites of Apis cerana were found amongst 18 species of plants belonging to 15 families (12 species in lowlands and seven species in highlands). Most of the nests were placed on Cocos nucifera (coconut) treesin lowland sites, and on Erythria variegata (dadap) in highland sites. Nests were also found to be located mostly in the cavities of trees with diameter 21-60 cm. Nest entrances were located at 228.31 cm above ground surface (ags) in highland and at 116.04 cm agsin lowlands. The nest entrances in highlands measured 12.21 by 3.73 cm (height and width), and in the lowlands 14.93 by 7.36 cm. The percentage of tree cavities used for nesting was statically higher in lowland (40.73%) compared to high land (17.86%), but it fluctuated very slightly in both high or lowland areas during observation. The percentage of trees with nests decreased in December and January but increased in February, with the same patterns found in both high and lowlands. Our research suggests that higher tree diversity in polyculture plantations promotes increased use by honeybees for nesting. Thus, the more tree diversity in polyculture plantations the better it could conserve natural honey bees populations.